THE ORAL RINSING HABT WITH WATER AFTER EATING FOOD SUGARY FOOD CAN REDUSE OCCURING OF DENTAL CARIES - Anak Agung Gede Agung (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Dental caries is a disease that is still be a health problem in Indonesia. The high prevalence of caries amongst permanen teeth of Indonesia people associated with the patterns of consumption sugary foods and the tooth brushing behavior that are not good. When tooth brushing at a certain moment had not alone do one of the way that can be done by oral rinsing with water after eatingt sugary foods. The aim this study to determine the correlation between the oral rinsing habit with water after eating sugary foods with the occuring risk of caries on permanent teeth of twelve years old children in Denpasar.This observational study with case control design used 144 respondents as the samples that were divideed into case and control were 72 responden for each. Data of case were obtained from the result of survey by UKS program in Puskesmas Densel IV and systematic random sampling for control samples. The data were analysed using univariate and bivariate by chi-square. The habit of oral rinsing with water after eating sugary foods can reduce occuring risk dental caries is 3,250 just than the respondents who do not have the oral rinsing habit with water after eating sugary fodds. Oral rinsing with water after take a meal can dissolve carbohydraths that attched on the tooth surface so the oral rinsing habit with water after eating sugary foods can reduce occuring risk of dental caries. The suggestion is if do not have time for tooth brushing so can do by oral rinsing with water.